Nutrition and Fiber Fraction Analysis of Fermented Water Hyacinth Plants Using Various Probiotics as Alternative Beef Cattle Feed - Muhammad Mukhtar (Jambura Journal of Animal Science, 2022)
Apart from being a bioaccumulator, several studies have also proven that water hyacinth has the potential to be an ingredient for animal feed and organic fertilizer because it contains amino acids and other nutritional elements. This research consists of 2 stages. The first stage is the effect of using several probiotics for fermented water hyacinth on nutritional quality and fiber fraction. The 4 types of probiotics used were liquid organic supplements (SOC), burger feed sauce (SBP), microbacter alfaafa 11 (MA-11), and effective microorganisms 4 (EM-4). The use of a liquid dose of each probiotic is 5 ml/1 kg of fresh water hyacinth. The second stage is the effect of the use of probiotic levels of SOC on the nutritional quality and fiber fraction of fermented water hyacinth. The levels of SOC probiotics used were 5 ml, 10 ml and 15 ml for every 1 kg of fresh water hyacinth ingredients.The use of 4 types of probiotics, namely SOC, SBP, MA-11 and EM-4, had a significantly affected in increasing the nutritional content of fresh water hyacinth ingredients, were the percentage of protein, the percentage of crude fat and the percentage of extracts without nitrogen. In this study, the 4 probiotics were able to reduce the fiber fraction, were acid detergent fiber, neutral detergent fiber, hemicellulosa, cellulose and lignin, and also changing the structure of the fiber fraction where the fresh water hyacinth material is a recommendation to be used as an alternative to beef cattle feed. The nutrient content and fiber fraction of the fermented water hyacinth is close to the nutrient content and fiber fraction of natural grasses. The increasing use of probiotic SOC levels will also increase the content of crude protein, crude fat and extracts without nitrogen from 5% to 15% SOC levels. In the fiber fraction, namely hemicellulose, cellulose and lignin in general, the results were significant only at the 5% level.